Automation of thermofixation in the production of reflective clothing (reflective DTF) - Panchenko, N.; Sotnik, S. (ХНУРЕ, 2026)
The work is devoted to the problem of ensuring the quality of reflective clothing elements manufactured using Reflective DTF technology. The technological process of applying reflective coatings is considered, and the critical dependence of the preservation of the optical properties of microspheres on the accuracy of the temperature regime at the thermofixation stage is revealed. A comparative evaluation of automatic temperature control methods is carried out according to the criteria of accuracy, speed, adaptability, and implementation complexity. Робота присвячена проблемі забезпечення якості світлоповертальних елементів одягу, виготовлених за технологією Reflective DTF. Розглянуто технологічний процес нанесення світлоповертальних покриттів та виявлено критичну залежність збереження оптичних властивостей мікрокульок від точності температурного режиму на етапі термофіксації. Здійснено порівняльну оцінку методів автоматичного контролю температури за критеріями точності, швидкодії, адаптивності та складності реалізації. Визначено оптимальний підхід до автоматизації термофіксації для забезпечення стабільності виробничого процесу.
Автоматизація термофіксації у виробництві світлоповертального одягу (Reflective DTF)
Keywords: thermofixation; ретрорефлексія; мікрокульки; контроль температури; ПІД-регулювання; світлоповертальний одяг; Reflective DTF; термофіксація; retroreflection; microspheres; temperature control; reflective clothing